Towards a Sustainable Land Taxation Reform in Imo State, Nigeria - Nwanekezi, S. C.; Odenigbo, O. A.; Ugwu, M. O. (Archives of Current Research International, 2023)
Land taxation reform must be focused on suitable valuation, enhancing revenue, base coverage, collecting and providing adequate services to the taxpayers. States in Nigeria must combine the right mix of strategic reform coupled with policy and administrative interaction that ensures the expected outcome from the taxation reform. On this ground, this paper reviewed the land taxation reform in Imo State and its sustainability. The review noted that the lack of effective administration of land taxation has made tax reform unsustainable in many Nigerian States, including Imo. As stated, Imo state does not have any platform, which results in issues of identifying and assessing properties; these problems are worsened by inadequate enforcement of tax collection systems. Although land taxation is administrative-intensive; however, technological advancement, awareness of the benefit of effective reform, and improved fiscal and social methods can ensure sustainable land taxation reform.